Language Contact and Documentation / Contacto lingüístico y documentación - Comrie, Bernard; Golluscio, Lucía (De Gruyter, 2014)
Language Contact; Language Change; Linguistic Areas; Linguistic Typology; Language Documentation; Digital Archives; Language Maintenance; Spoken and Written Language